Pre-Service English Teachers’ Perception on Higher Order Thinking Skills (HOTS) in English Language Teaching - Armala, Intan; Fauzia, Endang; Asib, Abdul (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2019)
Higher order thinking skill is one of the important components for an individual to be able to solve new problems in the 21th century. In the revised Bloom’s taxonomy, HOTS is defined as an incision among the three top levels of ability in the cognitive dimension (analyzing, evaluating, creating), and 3 levels of knowledge dimension (conceptual, procedural, metacognitive). The aim of the present case study was to investigate pre-service English teachers’ perception on Higher Order Thinking Skills in English language teaching. A total of 15 pre-service English teachers in a university in Indonesia participated in this study. The research used questionnaire to collect the data. Data were analyzed using interpretative approach. The result showed that the pre-service English teachers have their perspective about higher order thinking skills by themselves. They are aware towards Higher Order Thinking Skills in English language teaching. They are involving some activities to encourage students in thinking skill. They believed that every student is capable to think critically.